2022
DOI: 10.3389/fimmu.2022.878320
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Multiple Co-Inhibitory Molecules on Malaria-Induced CD8+ T Cells Are Associated With Increased Function Instead of Exhaustion

Abstract: Activated cytotoxic CD8+ T cells can selectively kill target cells in an antigen-specific manner. However, their prolonged activation often has detrimental effects on tissue homeostasis and function. Indeed, overwhelming cytotoxic activity of CD8+ T cells can drive immunopathology, and therefore, the extent and duration of CD8+ T cell effector function needs to be tightly regulated. One way to regulate CD8+ T cell function is their suppression through engagement of co-inhibitory molecules to their cognate liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The murine LAG-3 + cells were suppressive irrespective of CD49b expression, and the frequency of LAG-3 + cells in various tissues dwindled to levels seen in naïve mice within days of anti-malarial administration, suggesting these were not long-lived memory cells. Unexpectedly, the co-inhibitory receptor-rich CD8 + T cells had enhanced antigen-specific cytotoxic function ( 143 , 144 ). Based on the presently available evidence, it can be concluded that Tr1-like cells prevent symptomatic malaria infection by protecting against immune-mediated pathology, as demonstrated in mice and humans ( 134 136 , 141 ).…”
Section: The Role Of Tr1-induced Tolerance In Infectious Disease Sett...mentioning
confidence: 99%
“…The murine LAG-3 + cells were suppressive irrespective of CD49b expression, and the frequency of LAG-3 + cells in various tissues dwindled to levels seen in naïve mice within days of anti-malarial administration, suggesting these were not long-lived memory cells. Unexpectedly, the co-inhibitory receptor-rich CD8 + T cells had enhanced antigen-specific cytotoxic function ( 143 , 144 ). Based on the presently available evidence, it can be concluded that Tr1-like cells prevent symptomatic malaria infection by protecting against immune-mediated pathology, as demonstrated in mice and humans ( 134 136 , 141 ).…”
Section: The Role Of Tr1-induced Tolerance In Infectious Disease Sett...mentioning
confidence: 99%
“…In light of recent advances in antibody-mediated blockade of these pathways [3,4], characterizing immune cells that participate in activating or inhibitory interactions may be of crucial importance to identify opportune targets and develop novel treatments. We and others discovered the expression of multiple co-inhibitory molecules on T cells in the mouse model of cerebral malaria by infecting C57BL/6 mice with Plasmodium berghei ANKA [5][6][7][8], making it an ideal model to establish a panel addressing these challenges. Here, we describe a novel panel and gating strategy to investigate expression of multiple co-inhibitory molecules and their respective ligands on T cells, B cells, NK cells, macrophages/ monocytes, neutrophils, and dendritic cells (DC) in mice.…”
Section: Introductionmentioning
confidence: 99%